Penerapan Wudhu yang Baik dan Benar Serta Hafalan Do’a Sehari-hari di Desa Kromong Jombang - Darmawan, Moh. Faridl; Roziqin, Muhamad Khoirur; Nuha, Muhamad Ulin; Nisa' , Fakhrun; Nazula, Nazula; Azmi, Nahdliyah Islamiyah; Hidayat, Peni Nur; Rohmati, Salsabila Aulia (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
Community service in Kromong Ngusikan Jombang Village was carried out to provide TPQ children with a deeper understanding of ablution procedures in accordance with the guidance of Islamic law and the practice of daily prayers. Through the lecture method, to provide basic insight, as well as educational games to make it easier for children to understand the material. This activity focuses on the process of direct understanding and practice. The results of the questionnaire data show that the average knowledge of TPQ Al Islamiyah children regarding the practice of ablution is at 39%, meaning that there are still many who do not properly understand the ablution procedures according to the guidelines. However, after the implementation of practice and guidance there was a jump to 82%, which reflects the effectiveness of this program in increasing children's abilities and awareness of the importance of performing ablution correctly. This increase not only shows the success of the learning method used, but also emphasizes the importance of repetition and direct practice. in understanding daily worship. The impacts include increasing children's knowledge, teacher innovation, and increasing enthusiasm for learning.